2020
DOI: 10.3390/w12113119
|View full text |Cite
|
Sign up to set email alerts
|

Estimating IDF Curves Consistently over Durations with Spatial Covariates

Abstract: Given that long time series for temporally highly resolved precipitation observations are rarely available, it is necessary to pool information to obtain reliable estimates of the distribution of extreme precipitation, especially for short durations. In this study, we use a duration-dependent generalized extreme value distribution (d-GEV) with orthogonal polynomials of longitude and latitude as spatial covariates, allowing us to pool information between durations and stations. We determine the polynomial order… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…In this regard, Ganguli and Coulibaly [12], Mélèse et al [43] showed that a Bayesian Hierarchical Model approach resulted in reliable credibility intervals for IDF curves. For the rd-GEV approach, we investigate a bootstrap-based method for estimating the uncertainty of d-GEV based return levels in a different study [9]. We also limited our study to using data with hourly frequency, resulting in the value of the (sub-hourly) ν parameter of the d-GEV to be artificially set to zero (what we called the rd-GEV).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this regard, Ganguli and Coulibaly [12], Mélèse et al [43] showed that a Bayesian Hierarchical Model approach resulted in reliable credibility intervals for IDF curves. For the rd-GEV approach, we investigate a bootstrap-based method for estimating the uncertainty of d-GEV based return levels in a different study [9]. We also limited our study to using data with hourly frequency, resulting in the value of the (sub-hourly) ν parameter of the d-GEV to be artificially set to zero (what we called the rd-GEV).…”
Section: Discussionmentioning
confidence: 99%
“…Another critical issue for future studies is to explore how different dependence structures could impact the performance of the estimation. Furthermore, a comparison with the recent developments in the use of covariates for the rd-GEV approach could result in better skill for such an approach compared with our current MS-GEV one [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following Ritschel et al [8] and Ulrich et al [9], we used the duration dependent GEV (d-GEV) to model i(d) with the distribution…”
Section: Using the Duration-dependent Gevmentioning
confidence: 99%